2018
DOI: 10.3329/bmjk.v50i1-2.35838
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in women with hyperemesis gravidarum admitted in a tertiary hospital

Abstract: Background: Hyperemesis gravidarum is the most severe form of nausea and vomiting in pregnancy with poor pregnancy outcome. Hormonal, psychological, immunological, and infection with H. pylori contribute to the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The prevalence of hyponatraemia in pregnancy has not been clearly stated in previous studies, and most of these studies have focused on the association of hyponatraemia with pre-eclampsia. Moreover, it is most often reported in the setting of hyperemesis gravidarum, which occurs mainly during the first trimester 3 , 4 . In a study on the outcomes associated with hyponatraemia in pregnancy, hyponatraemia was reported in 0.27% of all deliveries, with up to 9% of cases of pre-eclampsia associated with hyponatraemia 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of hyponatraemia in pregnancy has not been clearly stated in previous studies, and most of these studies have focused on the association of hyponatraemia with pre-eclampsia. Moreover, it is most often reported in the setting of hyperemesis gravidarum, which occurs mainly during the first trimester 3 , 4 . In a study on the outcomes associated with hyponatraemia in pregnancy, hyponatraemia was reported in 0.27% of all deliveries, with up to 9% of cases of pre-eclampsia associated with hyponatraemia 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatraemia can occur in pregnancy and is associated with some pregnancy outcomes, which usually depend on the speed of drop of sodium concentrations 2 , 3 . While its most common cause in the first trimester remains excessive vomiting (hyperemesis gravidarum) 4 , in the second half of pregnancy, it is usually due to pre-eclampsia. Low natraemia is associated with twin pregnancy, significant oedema in the woman and early onset of pre-eclampsia 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Ginger has a distinctive aroma that serves to reduce nausea and vomiting in pregnant women (Kabir et al, 2018). When consumed, ginger water can warm the body and provide a sense of comfort.…”
Section: Discussion a Decrease In The Scale Of Emesis Gravidarum In T...mentioning
confidence: 99%
“…4 A wide array of conditions is associated with hyponatraemia in pregnancy, hyperemesis gravidarum and preeclampsia the most common causes in the first and second half of pregnancy, respectively. 5 Treatment options for severe hyponatraemia due to syndrome of inappropriate antidiuretic hormone (SIADH) include fluid restriction, oral urea, hypertonic saline, oral salt tablets and vasopressin receptor antagonists. There is no safety data regarding the use of vasopressin receptor antagonists during pregnancy or breast feeding.…”
Section: Introductionmentioning
confidence: 99%